Effects of Lidocaine Infusion during Experimental Endotoxemia in Horses - Peiró, Juliana Regina [UNESP]; Barnabe, P. A. [UNESP]; Cadioli, Fabiano Antonio [UNESP]; Cunha, F. Q.; Lima, Valéria Marçal Felix de [UNESP]; Mendonca, V. H. [UNESP]; Santana, A. E. [UNESP]; Malheiros, E. B. [UNESP]; Perri, Silvia Helena Venturoli [UNESP]; Valadao, C. A. A. [UNESP] (Wiley-Blackwell, 2010)
BackgroundThe clinical efficacy of IV infusion of lidocaine for treatment of equine endotoxemia has not been studied.HypothesisLidocaine infusion after exposure to lipopolysaccharide (LPS) will inhibit the inflammatory response and have inhibitory effects on the hemodynamic and cytokine responses to endotoxemia.AnimalsTwelve horses.MethodsTwo equal groups (n = 6): saline (GI) and lidocaine (GII). In all animals, endotoxin (500 ng/kg body weight [BW]) was injected intraperitoneally over 5 minutes. Twenty minutes later, animals received a bolus of GI or GII (1.3 mg/kg BW) over 5 minutes, followed by a 6-hour continuous rate infusion of GI or GII (0.05 mg/kg BW/min). Treatment efficacy was judged from change in arterial blood pressure, peripheral blood and peritoneal fluid (PF) variables (total and differential cell counts, enzyme activities, and cytokine concentrations), and clinical scores (CS) for behavioral evidence of abdominal pain or discomfort during the study.ResultsCompared with the control group, horses treated with lidocaine had significantly lower CS and serum and PF tumor necrosis factor-alpha (TNF-alpha) activity. At several time points in both groups, total and differential cell counts, glucose, total protein and fibrinogen concentrations, and alkaline phosphatase, creatine kinase, and TNF-alpha activities were significantly different from baseline values both in peripheral blood and in PF.Conclusions and Clinical ImportanceLidocaine significantly decreased severity of CS and inhibited TNF-alpha activity in PF.
Keywords: Cytokines; Lipopolysaccharide; Peritoneal fluid; Polymorphonuclear cells